The Perceptions of Madhhab Scholars and the Indonesian Ulema Council (MUI) Regarding the Lawfulness of Non-Cash Gold Trading - Harianda Tanjung Tanjung; Nurdin N; Syaifullah S (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the perceptions of classical Sunni legal schools (madhÄhib) scholars and the Indonesian Council of Ulama (Majelis Ulama Indonesia/MUI) regarding the practice of non-cash gold trading. The study focuses on analyzing the differences in juristic (fiqh) argumentation between the views of classical madhhab scholars and the Indonesian Council of Ulama through DSN-MUI Fatwa No. 77 of 2010, which permits non-cash gold trading under certain conditions. The objective of this research is to analyze the normative foundations, legal Ê¿illah (effective cause), and methods of hadith interpretation employed by classical madhhab scholars and the Indonesian Council of Ulama through the DSN-MUI in responding to the legal status of non-cash gold trading, which arises from changes in the function of gold within the modern economic system. This research adopts a literature study approach using content analysis methods applied to classical fiqh literature of the legal schools and the text of DSN-MUI fatwas. The findings indicate that classical madhhab scholars generally regard gold as a ribÄwÄ« commodity possessing an athmÄniyyah (monetary) function; therefore, non-cash gold trading is considered impermissible. In contrast, the Indonesian Council of Ulama, through the DSN-MUI, applies an integrative and contextual model of hadith interpretation by emphasizing a shift in the legal Ê¿illah, namely the transformation of goldâ€™s function from a medium of exchange to an investment commodity. These findings demonstrate the dynamic nature of ijtihÄd in Islamic law, balancing fidelity to textual sources (naá¹£á¹£) with the demands of modern economic realities. This study underscores the importance of developing contextual and maqÄá¹£idÄ«-based methodologies of hadith interpretation as a foundation for Islamic legal reform that is adaptive and relevant to contemporary developments.